Green retrofitting of building using BIM-based sustainability optimization - Shizra Mughal,; Ali Raza Khoso,; Haris Najeeb,; Muhammad Sufyan Noor Khan,; Tauha Hussain Ali,; Shabir Hussain Khahro, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The construction industry consumes around 55 percent of Pakistan’s annual energy and is the country’s most energy-intensive sector. It is, therefore, significant to devise a novel and effective model of green retrofitting of current buildings based on Building Information Modelling (BIM) which aims to reduce building energy consumption to effectively meet diversified climatic concerns and to promote sustainable structures. This research aims to reform the existing building by modifying the design parameters for an inefficient building envelope based on BIM simulation and data optimization results to optimize the overall energy consumption. BIM tools, such as Autodesk Revit and DesignBuilder have been used for the evaluation of the optimized energy-efficient design by comparing different design alternatives. After a detailed analysis, this research has concluded that the existing building is consuming a high amount of annual energy. With the help of BIM tools, which possess advanced algorithms for an effective optimization process, a list of ‘green’ solutions i.e., optimal designs has been generated, out of which the optimal and cost-effective design saved 46% of energy in total. In this study, the design variables selection has been fulfilled according to the local environmental sustainability.